1997
DOI: 10.1097/00007890-199709150-00021
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Gene Polymorphism and Heart Transplant Rejection1

Abstract: We have identified a particular cytokine genotype that may confer susceptibility to increased levels of early rejection. Patients with a worse prognosis may be able to be identified pretransplant by DNA analysis of TNF-A, IL-10, and other gene polymorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
113
6
1

Year Published

2000
2000
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(126 citation statements)
references
References 8 publications
6
113
6
1
Order By: Relevance
“…TNF-a acts as a pro-inflammatory cytokine and has been implicated in both acute and chronic rejection in several organ allograft populations (10). Despite this strong association, we observed no significant differences in the distribution of TNFa genotypes between ethnic populations.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…TNF-a acts as a pro-inflammatory cytokine and has been implicated in both acute and chronic rejection in several organ allograft populations (10). Despite this strong association, we observed no significant differences in the distribution of TNFa genotypes between ethnic populations.…”
Section: Discussioncontrasting
confidence: 58%
“…We did observe, however, a difference in the allelic distribution of the TNF-a (A) allele in patients (p Ω 0.042) compared with healthy controls (Figure 2). Expression of this allele is associated with a six-to sevenfold increase in TNF-a transcription in vitro and a higher susceptibility for allograft failure (2,3,10). We also noted a significant association between the IL-2 polymorphic (G) allele and those presenting with FSGS.…”
Section: Cytokine Alleles and Genotypes Correlate With Endstage Renalmentioning
confidence: 57%
See 1 more Smart Citation
“…TNF2 was not associated with HLA A1, B8, and DR3, unlike in another study 17 and the allele frequency of TNF2 (0.037, nine of 238 alleles in this study) was much smaller than values reported for Caucasians (0.16-0.19). 16,20,25 This difference may be due to a difference of race, and partly explain the lower frequency of aGVHD in Japanese than in Western populations. 26,27 In this series, also, severe aGVHD occurred less frequently than has been reported in Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…19 It has been reported that post-heart transplant patients with A at IL-10-1082 (low IL-10) and with TNF2 (high TNF-␣) were susceptible to graft rejection. 20 Furthermore, IL-10·G, a microsatellite polymorphic region at −1064 of the IL-10 promoter, 21 was suggested to play a role in the development of SLE since the distribution of the IL-10·G allele differed between SLE patients and healthy controls. 22 Such reports prompted us to investigate whether the gene polymorphisms of TNF-␣ and IL-10 are associated with the incidence of either severe aGVHD or cGVHD.…”
mentioning
confidence: 99%